Implementation of Fundamental Movement Learning Gymnastics in Elementary Schools - Herman Chaniago; Wahyuningtyas Puspitorini; Yafi Velyan Mahyudi (Journal Of Sport Education (JOPE), 2024)
This research aims to study how students learn basic floor exercise movements in elementary school and the impact on physical and cognitive growth. The results of this research will provide guidelines for learning gymnastics in elementary schools and increase awareness of the importance of fun and interactive learning methods. The research method used in this action research is the Kemmis and McTaggart model. The research subjects were students from the second grade of elementary school aged between 8-9 years and totaling 27 children, consisting of 17 girls and 12 boys. The research instrument was an observation sheet related to students' responses during learning and basic gymnastics movement skills. The balance indicator obtained the highest average score, namely 84, twisting movement 79, rolling movement 72, and flexibility 75. From the results of the assessment, the average met the minimum criteria for student completeness in physical education learning. Meanwhile, the difference in assessments from cycle I and cycle II obtained a result of 2.868 which was greater than t0 2.755 and α (0.05). This research confirms that the implementation of basic gymnastics movements in elementary school students is effective in improving balance, coordination, and flexibility. It has a positive impact on student's physical development and should be integrated into the primary school sports curriculum. Research also confirms the important role of physical health in preparing children physically.